Penggunaan Bakteri Kitinolitik sebagai Agens Biokontrol Penyakit Busuk Batang oleh Rhizoctonia solani pada Tanaman Kedelai (Utilization of Chitinolitic Bacteria as Biocontrol Agent of Stem Rot Disease by Rhizoctonia solani on Soybean) - Andi Khaeruni; Abdul Rahman (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2012)
Biological control of stem rot disease caused by Rhizoctonia solani on soybean using chitinolitic bacteria is one of the environmentally friendly control methods of pathogen. The study was conducted to select chitinolitic bacteria and to test their ability to suppress stem rot disease and promote plant growth of soybean. A total of ten chitinolitic bacteria were tested in vitro, and five of isolates i.e: ST21e, SS12b, ST17c, ST27d, and ST26c found to have more than 30% suppression toward R. solani. In planta test under green house condition at six weeks after planting showed that soybean plants inoculated with ST27d and ST17c isolates had significantly lower disease incidence and had increased plant height and leaf number. Both of chitinolitic bacteria isolates are promising as biocontrol agents of stem rot disease caused by R. solani of soybean.Key words: biological control, chitinolitic bacteria, Rhizoctonia solani